2013
DOI: 10.1186/1748-717x-8-37
|View full text |Cite
|
Sign up to set email alerts
|

RapidArc, SmartArc and TomoHD compared with classical step and shoot and sliding window intensity modulated radiotherapy in an oropharyngeal cancer treatment plan comparison

Abstract: BackroundRadiotherapy techniques have evolved rapidly over the last decade with the introduction of Intensity Modulated RadioTherapy (IMRT) in different forms. It is not clear which of the IMRT techniques is superior in the treatment of head and neck cancer patients in terms of coverage of the planning target volumes (PTVs), sparing the organs at risk (OARs), dose to the normal tissue, number of monitor units needed and delivery time.The present paper aims to compare Step and Shoot (SS) IMRT, Sliding Window (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 42 publications
4
40
2
2
Order By: Relevance
“…The dose to the OARs, including the spinal cord and the brainstem, was kept as low as possible respecting the prescription to the PTV. The reference dose constraints have been reported in a preliminary planning study [30].…”
Section: Irradiation Techniquesmentioning
confidence: 99%
“…The dose to the OARs, including the spinal cord and the brainstem, was kept as low as possible respecting the prescription to the PTV. The reference dose constraints have been reported in a preliminary planning study [30].…”
Section: Irradiation Techniquesmentioning
confidence: 99%
“…Despite the number of dosimetric studies, these results should be interpreted carefully because the calculation algorithm and resolution of the planning systems are different (16,17). The algorithm used for each technique has some specificity due to delivery techniques.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is also expected that the relation of PTVs to swallowing critical organs can differ considerably among various studies. In the van Gestel study, 35 the authors explicitly excluded from the analysis some OARs as upper pharyngeal constrictor owing to a major overlap with the PTV, suggesting that the other swallowing OARs (as medium and lower pharyngeal constrictor and glottic and SGL) do not present major overlaps with PTVs. In our study, we have shown that the PCM and SGL present a median overlap of 96% and 56% with the low-risk nodal area, a situation that actually prevents a dose reduction in the low-intermediate range without compromising PTV coverage for most of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] This, despite the worldwide implementation of this technique, is gradually replacing fixed-field IMRT, thanks to its advantages in terms of treatment efficiency. VMAT planning optimization process is much more complex than fixed-field IMRT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation